Research on the Optimization of Public Facilities in Old Blocks of Guangxi: -- Take Kunshan Huayuan Community in Guilin City as an Example - Yang, Chenyu; Gong, Liyan; Zhang, Jian; Yang, Jiahui; Ren, Junru (Transactions on Social Science, Education and Humanities Research, 2023)
This paper builds on the problem that under the background of the aging society, the function of public facilities does not adapt to the growing life needs of modern society, especially it cannot meet the special environmental needs of the increasing number of elderly people. The project selects Kunshan Huayuan Community in Guilin city, which has the majority of the elderly, and strives to improve the low suitability of public facilities through aging design and sustainable design, insufficient supporting facilities for the elderly, and other problems in the travel activities of the elderly. In order to build aging public facilities system, can meet the needs of the elderly life entertainment, avoid the elderly away from the city from the city life and the disadvantages of physical and mental health, at the same time in the future design and planning actively deal with changing and growth of aging.